Analysis of Factors Affecting the Supply of Cafe Service Industry in Pekanbaru City - Subarjo, Indah Maharani (Global Insights in Management and Economic Research, 2025)
Purpose of the study: This study aims to identify and analyze key factors influencing the supply and operation of cafe service businesses in Pekanbaru City, Indonesia. Materials and methods: A quantitative approach was employed using survey data collected from 100 cafe owners/managers in Pekanbaru selected through purposive sampling. Data were analyzed using descriptive statistics and multiple regression analysis. Results: The findings indicate that transaction costs, servicescape investments, market demand patterns, and labor availability significantly influence cafe business operations in Pekanbaru. These factors collectively explain 54.7% of the variance in cafe supply decisions. Conclusions: The cafe industry in Pekanbaru is experiencing rapid growth influenced by both economic and social factors. Transaction costs particularly impact business sustainability, while servicescape investments significantly determine competitive positioning in the market.